Successful Vaginal Delivery after External Cephalic Version in a Woman with a Large Partial Uterine Septum - Kristen E. Park; Nicole L. Vestal; Michael S. Awadalla; Sharon A. Winer (Case Reports in Obstetrics and Gynecology)
Septate uteri have been associated with adverse pregnancy outcomes including spontaneous abortion, preterm delivery, and malpresentation. It is unclear if uterine septa are associated with infertility. Although some studies have shown improved pregnancy outcomes after septum resection, indications for resection are not well established. We describe a case of a woman with a large partial uterine septum diagnosed during workup for infertility who conceived without septum resection. Both of her subsequent pregnancies were initially breech presentations for which the patient underwent external cephalic version followed by full-term vaginal deliveries. This case adds evidence that an unresected uterine septum should not be considered a contraindication to external cephalic version.